Copper bromide vapour laser with an output pulse duration of up to 320 ns; Quantum Electronics; Vol. 46, № 1 - Gubarev F. A. Fedor Aleksandrovich; Fedorov V. F. Valery Fedorovich; Fedorov K. V. Kirill Valerjevich; Shiyanov D. V. Dmitry Valeryevich; Evtushenko G. S. Gennady Sergeevich (2016, 2016)
Title screen